Studies on Physicochemical Analysis of Water from Different Sources - Keerthika, D.; Gokulpriyan, K.; Harini, I.; Karthikeyan, Dr. V. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Introduction: Water is one of the important natural sources for all living organisms. It is one of the ecological systems. It’s the essential source for human health, food production and economic development. The quality of water is important is an important parameter to be noted. The quality of water is affected by various contaminants. The consumption of contaminated water may cause serious health problems due to the activity of microorganism present in it .Due to the activity of microorganism the quality of water becomes very poor and also causes harmful diseases. Thus in this study we are aimed to test the quality of water from different sources by means of physicochemical studies. Objectives: The objective of the present studies is to provide information on the physicochemical characteristics & detailed ecological studies of Portable water and Lake water (Habitat) in order to discuss it’s suitability for human consumption. Physicochemical aspects of the water have been investigated to assess the quality of water. Result: The variations of physicochemical properties and comparative analysis of water different sources were analyzed.